2014
DOI: 10.1111/luts.12073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Work‐Related Factors on Lower Urinary Tract Symptoms in Nurses and Secretaries

Abstract: There is a vicious circle between symptoms and work conditions. To prevent the working women from harmful effects of this circle, the employers should be aware of this health problem; working conditions should be improved; educational programs for LUTS should be organized and the working women should be encouraged to go to the health providers to seek treatment when the symptoms occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 29 publications
(56 reference statements)
3
38
1
Order By: Relevance
“…The instruments used for evaluation varied widely, with 13 studies using validated instruments and one study using a questionnaire designed and prepared by the authors (Tables , , and ) . Four studies used the Medical Outcomes Study 36‐item Health Survey (SF‐36) and all four found that social functioning was the subscale most affected, followed by physical health and general health (Tables and ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The instruments used for evaluation varied widely, with 13 studies using validated instruments and one study using a questionnaire designed and prepared by the authors (Tables , , and ) . Four studies used the Medical Outcomes Study 36‐item Health Survey (SF‐36) and all four found that social functioning was the subscale most affected, followed by physical health and general health (Tables and ) …”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the prevalence was shown to be high among nursing staff, with the most frequently investigated symptoms being unspecified UI, SUI, UUI, MUI, and OAB. While the prevalence of LUTS ranges from 25.0% to 61.1% among women, in female nurses the rates ranged from 15.2% to 90.5% . This is directly related to nurses’ behaviors in the workplace, such as heavy lifting and toileting behavior, with these factors associated with urinary symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Six publications focused on OAB, including three that used validated OAB measures . Five publications reported general LUTS, and all five used validated LUTS measures . Other publications focused on daytime frequency, UTIs, and one on nocturia .…”
Section: Resultsmentioning
confidence: 99%
“…13 Studies also varied in the type of bladder symptoms reported, the frequency of the symptom recorded, and the use of validated measures to ascertain symptoms (Table 1). UI was the most common bladder symptom reported in 30 publications, [11][12][13][14][15][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][42][43][44][45][46] 7 of which used validated UI measures. 21,26,28,37,38,42 Six publications focused on OAB, 15,22,31,33,44,47 including three that used validated OAB measures.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, 67.3% of female nurse practitioners surveyed in the USA ( N = 113, mean age 43 years) delayed voiding when busy (Palmer & Newman, ) and it was again the most common “unhealthy bladder habit” in Chinese female clinical nurses ( N = 636; mean age 31 years) (Wan et al, ). Finally, female Turkish nurses were reported to have “poorer bladder habits” (although habits were not clearly defined) compared with secretaries, the authors concluding that where job control is low, prolonged voiding intervals are likely (Kaya et al, ). Clearly, delayed voiding is a common international phenomenon for female nurses in many roles and settings.…”
Section: Discussionmentioning
confidence: 99%